2016
DOI: 10.3390/toxins8010013
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Microfluidic Assay for the Detection of Botulinum Neurotoxin in Animal Sera

Abstract: Potent Botulinum neurotoxins (BoNTs) represent a threat to public health and safety. Botulism is a disease caused by BoNT intoxication that results in muscle paralysis that can be fatal. Sensitive assays capable of detecting BoNTs from different substrates and settings are essential to limit foodborne contamination and morbidity. In this report, we describe a rapid 96-well microfluidic double sandwich immunoassay for the sensitive detection of BoNT-A from animal sera. This BoNT microfluidic assay requires only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…BoNT detection assays utilize multiple methods including antibody-based, mass-spectrometry, nucleic acid-based, cell-based, and enzymatic assays, as well as in vivo and ex vivo mouse assays in buffer and some matrices [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. All of the current technologies have advantages and disadvantages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BoNT detection assays utilize multiple methods including antibody-based, mass-spectrometry, nucleic acid-based, cell-based, and enzymatic assays, as well as in vivo and ex vivo mouse assays in buffer and some matrices [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. All of the current technologies have advantages and disadvantages.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, newer assays have combined different technologies to improve the sensitivity of detection. Depending on the assay, the detection limits range from sub-picogram to nanogram per mL or attomolar to pM for buffer and some food matrices [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…A variety of methods have been described for detection of BoNTs (Singh et al, 2013 ; Koh et al, 2015 ; Babrak et al, 2016 ; Cheng et al, 2016 ), but only a small subset of these methods have undergone inter-laboratory validation of their performance criteria in different food, environmental, and clinical sample matrices, which is prerequisite for deploying any assay for use in public health laboratories. Detection criteria and requirements for various botulinum neurotoxin detection methods for different applications are represented in Table 1 .…”
Section: In Vitro Methods For Detection Of Bonts and Neurotomentioning
confidence: 99%
“…Another group (Novo et al, 2013) demonstrated PDMS microfluidics with integrated silicon photodiodes for the chemiluminescence detection of OTA in wine and beer. The microfluidic Babrak et al (2015) device had two U-shaped channels to simultaneously analyze a reference solution and an OTA contaminated solution. The LOD for the beer and red wine extracts were 0.1 and 2 ng/mL, respectively.…”
Section: Food Safetymentioning
confidence: 99%
“…The study detected pesticide residues with lower LOD by using the microfluidic chamber. Babrak et al (2015) developed a 96-well microfluidic immunoassay plate device for the detection of Botulinum neurotoxins (BoNTs). Each well of the plate consisted of a tapered spiral microchannel that provided increased surface area, faster reaction kinetics, and occupied only 5 µl of sample volume.…”
Section: Food Safetymentioning
confidence: 99%